Development and validation of a TRP-related gene signature for overall survival prediction in lung adenocarcinoma - He, Min; Wu, Gujie; Wang, Ziheng; Ren, Kuan; Yang, Zheng; Xue, Qun (Frontiers in Genetics, 2022)
The transient Receptor Potential (TRP) channel is a type of channel protein widely distributed in peripheral and central nervous systems. Genes encoding TRP can be regulated by natural aromatic substances and serve as a therapeutic target for many diseases. However, the role of TRP-related genes in lung adenocarcinoma (LUAD) remains unclear. In this study, we used data from The Cancer Genome Atlas (TCGA) database to screen and identify 17 TRP-related genes that are differentially expressed between LUAD and normal lung tissues. Based on these differentially expressed genes (DEGs), we classified all patients with LUAD into two subtypes. Significant differences in prognosis, clinical features, and immune cell infiltration characteristics were observed between the two subtypes. Subsequently, a prognostic signature with 12 genes was established by applying the Least Absolute Shrinkage and Selection Operator (LASSO) Cox regression method, and all patients with LUAD were classified into low- or high-risk groups. Patients with LUAD in the low-risk group had a significantly longer survival time than those in the high-risk group (p < 0.001), which was confirmed by LUAD data from the validation datasets GSE72094 and GSE68571. Combined with clinical characteristics, the risk score was found to be an independent predictor of overall survival (OS) in patients with LUAD. Additionally, patients with high TRP scores exhibited poorer clinical characteristics and immune status, while showing a sensitive response to chemotherapeutic agents. In conclusion, the TRP score is a promising biomarker for determining the prognosis, molecular subtype, tumor microenvironment, and guiding personalized treatment in patients with LUAD.